Hyperprofessionalized and commodified : a case study examination of FBS bowl games and the utilization of football players as programmatic promotional material - Corr, Chris; Southall, Richard M.; Southall, Crystal; Hart, Richard J. (London : Human Kinetics, Inc., 2023)
Football Bowl Subdivision (FBS) football games are presented in a hypercommercialized manner by television broadcast networks through the targeted use of in-game graphics and corporatized content. While commercialized FBS football broadcast components have been analyzed within the frameworks of a hypercommercialized National Collegiate Athletic Association and media institutional logics, an analysis of commentator language has yet to be examined within the larger institutional ﬁeld of FBS football broadcasts. Utilizing agenda setting and media framing as frameworks, this case study examined the manner in which commentators frame FBS football players as professionals in a hypercommercialized institutional setting. From a sample of 18 FBS bowl games during the 2019–20 season, discourse and thematic analysis reveal that commentators frame FBS football players in the context of their future professional opportunities (i.e., National Football League). The framing of FBS football players as professionals aligns with extant literature examining the broader institutional ﬁeld of broadcast media and logics pervasive in the National Collegiate Athletic Association as an organization. The commodiﬁcation of FBS football players as integral components to strategic programmatic content promoting future broadcast programming is discussed.Keywords: agenda setting, ESPN, Football Bowl Subdivision, media framing, institutional logics, commodiﬁcation.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Football players -- Economic aspects -- Case studies; Television broadcasting of sports -- Marketing -- Case studies